Pediatric use of tetracyclines: focus on neurodevelopmental effects - Inta, Ioana; Hoffmann, Georg F.; Bettendorf, Markus (Pediatric research, 2017)
Pediatric use of tetracyclines: focus on neurodevelopmental effects